1983
DOI: 10.1128/iai.40.2.514-522.1983
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and suppression of immunity to herpes simplex virus: different presentations of antigens induce different types of suppressor cells

Abstract: In this report, we examine tolerance (hyporesponsiveness) and suppression of delayed hypersensitivity (DH) to herpes simplex virus (HSV) in mice, using two different forms of tolerogen: HSV particles and HSV-infected spleen cells. The intravenous injection of mice with either HSV particles or spleen cells 7 days before subcutaneous immunization with virus induced a profound state of unresponsiveness. This unresponsive state was mediated, at least in part, by suppressor T cells (Ts), which were demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…In that study, they demonstrated that suppression of the HSV-DTH response by T suppressor cells inhibited the immunopathological damage. Many others have also demonstrated that the HSV-specific DTH reaction is subject to modulation by suppressor cells at either the afferent or efferent level (21,29). In our CD8+-depleted mice, we could still demonstrate potent DTH reactions although, perhaps unexpectedly, these were not increased in magnitude over those observed in nonsuppressed mice.…”
Section: Discussionsupporting
confidence: 42%
“…In that study, they demonstrated that suppression of the HSV-DTH response by T suppressor cells inhibited the immunopathological damage. Many others have also demonstrated that the HSV-specific DTH reaction is subject to modulation by suppressor cells at either the afferent or efferent level (21,29). In our CD8+-depleted mice, we could still demonstrate potent DTH reactions although, perhaps unexpectedly, these were not increased in magnitude over those observed in nonsuppressed mice.…”
Section: Discussionsupporting
confidence: 42%
“…T,-aff block the early afferent phase of the DH response involving the induction and clonal expansion of DH-mediating T cells. T,-eff, on the other hand, act later in the efferent phase by blocking the expression of primed DH-mediating T cells (13). Both T, are virus-specific in their action; i.e., T, raised in mice with HSV-induced tolerance did not affect the DH response to a different virus, vesicular stomatitis virus.…”
mentioning
confidence: 97%
“…In most of these studies the coupled antigen has been a simple hapten. Recently, we have described the induction of tolerance mediated by Ts by using lymphoid cells coupled with a complex antigen, namely herpes simplex virus (HSV) (13). Spleen cells (SC) infected with HSV when injected intravenously (i.v.)…”
mentioning
confidence: 99%
See 2 more Smart Citations